Pharmaceutical regulation and health policy objectives - Laura Birg (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
This paper analyzes a maximum price system and a reference price system in a vertical differentiation model with a brand-name drug and a generic. In particular, both instruments are compared with respect to their performance in reducing public expenditure, limiting financial exposure of patients, improving access to pharmaceuticals, and stimulating competition. For identical regulatory prices, free pricing under the reference system tends to result in a higher price for the brand-name drug. For identical price reductions of the brand-name drug, the lower reimbursement amount under the reference price system results in lower health expenditure, but higher financial exposure of patients. Total welfare is higher under the maximum price system.
Keywords: I18; L50; H51; 330; pharmaceutical regulation; reference price; maximum price; price cap; health; policy objectives